Blastocyst score, a blastocyst quality ranking tool, is a predictor of blastocyst ploidy and implantation potential - Qiansheng Zhan, M.D., Ph.D; E.T. Sierra, Ph.D; Jonas Malmsten, Ph.D; Zhen Ye, M.S; Zev Rosenwaks, M.D; Nikica Zaninovic, Ph.D (Elsevier, 2020)
Objective: To convert blastocyst (BL) morphological grade and BL day into a numeric blastocyst score (BS). Design: Retrospective cohort study. Setting: Academic center. Patient(s): A total of 5,653 BL of known implantation (fetal heart, FH) and 11,348 biopsied BL. Intervention(s): Based on their FH rates and/or significance, a score (1-4) was assigned to each BL grade component. The BL morphological score (BMS) is the sum (BS = BMS on day 5; BS = BMS + 2 on day 6). Main Outcome Measure(s): Statistics characterized the FH and euploidy odds with BS. Result(s): All three morphology grade components and BL day were associated with implantation and euploidy probability. The FH rate and euploidy odds decrease with larger BS. The BS was the most important factor (odds ratio [OR] per unit change = 0.807, 95% confidence interval [CI] 0.784, 0.831) for untested and euploid BL implantation, and the sole one for euploid BL (OR/unit change = 0.845, 95% CI 0.803, 0.889). The BS is the second most significant factor after maternal age for euploidy probability (OR/unit change = 0.808, 95% CI 0.795, 0.822). In training and validation sets (75:25), the BS can predict implantation with similar area under the curve [AUC] (training = 0.628, 95% CI 0.613, 0.643; validation = 0.606, 95% CI 0.581, 0.631). The BS has better euploidy prediction ability (training AUC = 0.683, 95% CI 0.673, 0.693; validation AUC = 0.698, 95% CI 0.681, 0.715). The BS can stratify BL into good (3-5), fair (6-9), and poor (10-14) groups, reflecting their FH, live birth rates, and ploidy status. Advanced maternal age was associated with lower untested BL implantation and lower euploidy odds across all groups. Conclusion(s): The BS is a predictor of BL ploidy and FH implantation.